Bibliometric Analysis on Ocean Literacy Studies for Marine Conservation - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The aim of this study is to present an overview of the current scientific literature pertaining to ocean literacy. We applied a bibliometric method to examine relational patterns among publications in a set of 192 papers indexed from 2004 to 2023 in Web of Science Core Collection, applying Price’s, Lotka’s, Bradford’s, and Zipf’s bibliometric laws to add more validation to VOSviewer and processing both data and metadata. The findings indicate a significant exponential growth in scientific output from 2004 to 2022 (R2 = 86%), with a substantial amount of scientific research being focused on ocean literacy. The analysis shows the thematic trends of terminologies such as knowledge and citizen perception of climate change in relation to oceans; the benefits of biodiversity management and ocean conservation; and ocean education and its relation to behavior and attitudes towards and awareness of oceans. The research and its theoretical perspectives prompt an investigation of the impacts of ocean literacy outside of education, thanks to the contributions of authors from more than fifty countries dedicated to the study of these activities. © 2023 by the authors.